Paixões e cores da torcida baré: significados sociais do ato de torcer por um time de futebol profissional em Manaus - (:unkn) unknown (Universidade Federal do Amazonas, 2013)
This study presents a discussion of symbolic meanings present in local practices cheerleaders. The research objective was to investigate the social meanings of twist for a professional football team in Manaus. To carry out our research we assume that the initial twist is seemingly simple, seen through the prism of references and identity standards of the population, however, immersed in this apparent simplicity, and in addition to the sports events are present dynamics of intense relations passion, social and cultural meanings ample, where their signs bring with them a symbolic universe that say a lot about the Brazilian society and Manauense so particular. Our research was characterized as an ethnographic study and data collection were used as instruments, questionnaires, semi-structured interviews and a field journal. To decode the discourse of the interviewees and extract from them the essence of the phenomenon, we used discourse analysis. In order to unravel the social meanings present in the twist were chosen cheerleaders who cheer the teams, because despite the current state of football amazonenense they exist and have local representation. The data collection of the research involved fans organized cheerleading Alvinegro the Empire Athletic Club Rio Negro, the organized supporters Narraça the National Football Club and the fans organizes Hurricane Blue São Raimundo Esporte Clube. Besides the organized fans were also part of this research the ordinary fans, in order to ascertain their perceptions of the meanings of the twist and these differed from the perception of organized supporters, as well as to know which teams of your choice. The study revealed that the twist to manauenses football fans, who mostly twist primarily by professional clubs of the State of Rio de Janeiro, plays an important role in the social life of the same forms of socialization and identification symbolically present and for its ability to generate exciting and thrilling moments, within a highly regulated and standardized daily
Keywords: Futebol - Aspectos sociais; Football - Social aspects; Clubes de futebol - Manaus; Football clubs - Manaus; OUTROS